NMR of α-synuclein-polyamine complexes elucidates the mechanism and kinetics of induced aggregation - Fernández, C.O. (2004)
The aggregation of α-synuclein is characteristic of Parkinson's disease (PD) and other neurodegenerative synucleinopathies. The 140-aa protein is natively unstructured; thus, ligands binding to the monomeric form are of therapeutic interest. Biogenic polyamines promote the aggregation of α-synuclein and may constitute endogenous agents modulating the pathogenesis of PD. We characterized the complexes of natural and synthetic polyamines with α-synuclein by NMR and assigned the binding site to C-terminal residues 109-140. Dissociation constants were derived from chemical shift perturbations. Greater polyamine charge (+ 2 → + 5) correlated with increased affinity and enhancement of fibrillation, for which we propose a simple kinetic mechanism involving a dimeric nucleation center. According to the analysis, polyamines increase the extent of nucleation by ∼104 and the rate of monomer addition ∼40-fold. Significant secondary structure is not induced in monomeric α-synuclein by polyamines at 15°C. Instead, NMR reveals changes in a region (aa 22-93) far removed from the polyamine binding site and presumed to adopt the β-sheet conformation characteristic of fibrillar α-synuclein. We conclude that the C-terminal domain acts as a regulator of α-synuclein aggregation.